Development of Compact P-Band Vector Reflectometer - Yi Lung Then; Kok Yeow You; Ming Hao Lee; Chia Yew Lee (International Journal of Electrical and Computer Engineering (IJECE), 2017)
A compact and low cost portable vector reflectometer is designed for a reliable measurement of reflection coefficient, S11. This reflectometer focuses on return loss measurement of frequency ranges from 450 MHz to 550 MHz. The detection of magnitude and phase is based on the utilization of surface mount Analog Devices AD8302 gain/phase detector. The data acquisition is controlled by using Arduino-Nano 3.0 microcontroller, with the use of two analog to digital converter (ADC) and a digital to analog converter (DAC). One port (Open, short and matched load) calibration technique is used to eliminate systematic errors prior to data acquisition. The evaluation of the reflectometer is done by comparing the result of the measurement to that of vector network analyzer.